Integrating quality improvement into the ECHO model to improve care for children and youth with epilepsy. (29th August 2020) - Joshi, Sucheta; Gali, Kari; Radecki, Linda; Shah, Amy; Hueneke, Sarah; Calabrese, Trisha; Katzenbach, Alexis; Sachdeva, Ramesh; Brown, Lawrence; Kimball, Eve; White, Patience; McManus, Peggy; et al.
Abstract: Objective: Project ECHO (Extension for Community Healthcare Outcomes), a telementoring program, utilizes lectures, case‐based learning, and an "all teach–all learn" approach to increase primary care provider (PCP) knowledge/confidence in managing chronic health conditions. The American Academy of Pediatrics (AAP) Epilepsy and Comorbidities ECHO incorporated quality improvement (QI) methodology to create meaningful practice change, while increasing PCP knowledge/self‐efficacy in epilepsy management using the ECHO model. Methods: Monthly ECHO sessions (May 2018 to December 2018) included lectures, case presentations/discussion, and QI review. Pediatric practices were recruited through the AAP. Practices engaged in ECHO sessions and improvement activities including monthly Plan‐Do‐Study‐Act cycles, team huddles, chart reviews, and QI coaching calls to facilitate practice change. They were provided resource toolkits with documentation templates, safety handouts, and medication side effects sheets. QI measures were selected from the American Academy of Neurology Measurement Set for Epilepsy. The AAP Quality Improvement Data Aggregator was used for data entry, run chart development, and tracking outcomes. Participants completed retrospective surveys to assess changes in knowledge and self‐efficacy. Results: Seven practices participated across five states. Average session attendance was 14 health professionals (range = 13‐17). A total of 479 chart reviews demonstrated improvement in six of seven measures: health care transition (45.3%, P  = .005), safety education (41.6%, P  = .036), mental/behavioral health screening (32.2% P  = .027), tertiary center referral (26.7%, not significant [n.s.]), antiseizure therapy side effects (23%, n.s.), and documenting seizure frequency (7.1%, n.s.); counseling for women of childbearing age decreased by 7.8%. Significance: This project demonstrated that integrating QI into an ECHO model results in practice change and increases PCP knowledge/confidence/self‐efficacy in managing epilepsy.